Measuring the Rise of Gun Violence Across Presidential Administrations in Mexico - Eugenio Weigend; Rukman Bhatia (Washington University Journal of Law & Policy, 2019)
There is evidence that the overall volume of firearms in Mexico has increased, directly impacting the rise of homicides and costs on the population. Missing from the discussion, however, are simple metrics that indicate by how much both rates and proportions of gun violence have altered across the years in Mexico. To contribute to the discussion, this article analyzes changes in both the rates and the percentages of crimes committed with a gun in Mexico, specifically examining the levels of gun violence across the last three presidential administrations.
Keywords: gun violence; Mexico; presidential administrations; firearms